Pengajuan Soal Matematika Siswa SMP pada Materi Aritmetika Sosial Ditinjau dari Tipe Kepribadian Ekstrovert-Introvert - Dewi, Annisa Rifka; Masriyah, Masriyah (MATHEdunesa, 2024)
Problem posing is an important role in mathematics learning. By using problem posing activities in mathematics learning, teachers can find out how much students understand the material being taught. The aim of this research is to describe the mathematics problem posed for junior high school students on social arithmetic material viewed from the extrovert-introvert personality types. This is a descriptive qualitative research and the subjects are two students of junior high school. Data were collected through a questionnaire, mathematics ability test, problem posing tests, and interviews. The results of the study showed that extrovert and introvert subjects could pose problems through all three process of problem posing. Extrovert student tent to ask fewer questions than introvert student, but they were more likely to relate personal experiences to assignment information in the process of asking questions. On the other hand, introvert student tent to ask more questions, especially at the translating stage, with a focus on remembering and relating previous material.